Effectiveness of innovative value-oriented marketing solutions on dairy market - Stets, O.; Krykavskyy, Ye. (Lviv Politechnic Publishing House, 2017)
It has been found that optimum distribution of incomes has undergone certain transformational changes in current market conditions. Thus, internationally, the largest share of income (60 %) is the salary, while in Ukraine it makes only up to 35% of the total income. Other 65 % comes from other sources. The purchasing power of the population is an important factor. In general, it has been proved (based on the average salary) that Ukrainians spend more than 50 % of their income on food. Main suppliers and brands operating on the Ukrainian dairy products market (Molokiya™, Yagotynske™, Bila Linia™, Voloshkove Pole™, Slovianochka™, Activia™, Prostokvashino™, Galychyna™) have been assessed under such criteria as target audience, consumption purpose and product value. It has been established that there is a segment of premium goods consumers on the milk market who are ready to pay more for high quality products. The expediency of introducing non-traditional methods of competition on the fast moving consumer goods markets has been substantiated. The most common example of such market is the market of dairy products, which are reasonably priced and have high level of nutrients, ensuring proper, normalized human diet. The effectiveness of implementing innovative solutions to the marketing-mix development has been identified, the solutions focusing on such human values as natural and healthy food, environmentally friendly attitude (Fresh Milk technology, Pure-Pak Sense Aseptic packing). It has been established that due to active use and modification of traditional marketing tools, Ternopil Dairy Factory PJSC (Molokiya™) showed impressive results as for the market share and geographic coverage of the market. The basis of these decisions was valueoriented approach, i.e. focusing marketing activities not only on the product and the customer, but also on the traditional human values that are often not directly related to any goods or consumers. These are the following three topical areas: – in the product policy – creation and/or modification of the products included in the healthy food diet with maximum preservation of natural properties; – in the distribution policy – dramatic shortening of the production-consumption cycle, resulting in a very slight loss of natural properties, thus, radical reduction of the requirements for protective functions of packaging; – in the distribution policy – maximum convenience of dairy products complete use and packaging recycling.
Keywords: dairy market; marketing-mix innovative solutions; human values; 338.43; 658.4